The impact of elephants (Loxodonta africana) on the Baobab (Adansonia digitata) in a semi-arid savanna - Amanda Khosa; Hilton G.T. Ndagurwa; Ed T.F. Witkowski; Simbai A. Mutematemi; Admire T. Mrewa; Josephine Zisadza; Tatenda Nyenda; Justice Muvengwi (Global Ecology and Conservation, 2023)
The impacts of the expanding African elephant (Loxodonta africana) population in southern Africa leads to a shift in savanna vegetation community composition and structure. However, little has been done to understand the effect of elephants on the structure of keystone tree species like the baobab. We sampled two protected areas in Southeast lowveld of Zimbabwe to quantify the impact of elephants on the baobab (Adansonia digitata L.), one area with elephants (Save Valley Conservancy: SVC) and the other without elephants (Chipinge Safari Area: CSA). Data on elephant damage, baobab density, and structural variables (tree height, stem basal area, and canopy cover) were collected in seven 1 km2 plots. Baobab damage was classed into four categories, i) new, ii) old, iii) very old, and iv) none, to have a time series interpretation. Distances of every baobab tree from spatial variables, nearest management road, perennial water source and conservancy boundary were measured. Baobabs in the absence of elephants (CSA) were taller with higher basal area and canopy cover than those where elephants were present (SVC). Although SVC baobabs had smaller structural variables compared with CSA, their density was much higher 1.69 ha-1 compared with 0.94 ha-1 for CSA. More baobabs in the smaller size classes for SVC suggests that recruitment was higher than CSA. No elephant damage was observed in the CSA although 23 % of baobabs showed signs of very old harvesting of bark by humans. All trees in SVC showed signs of elephant damage in either trunks or canopies, with most of damage classed as very old. Baobab damage decreased with distance from roads and perennial water sources while it increased with distance from conservancy boundary. Our results demonstrate that elephants have a great impact on baobab structure but not necessarily recruitment as indicated by the presence of some baobabs in smaller size classes, suggesting that other factors may be more important in determining recruitment of this keystone species.